SISTEM TRANSMISI DATA GULA DARAH BERBASIS ARDUINO - Ika Puspita (Politeknik Harapan Bersama Tegal, 2020)
Abstract – This study aims to design an interface that connects blood sugar measurement devices with mobile phones and design a database system and visual display for monitoring blood sugar levels in the patient's body. This monitoring system integrates several tools used to transmit data measuring the results of blood sugar. On the patient side there is a glucometer, arduino, along with bluetooth and android-based mobile phones that will be used to send measurement data to the web server so that it can be accessed by doctors to monitor the development of the patient's health condition. Based on observations obtained an error value of 23.33% for 60 seconds of observations, an error of 32% for observations for 90 seconds, and an error of 31.11% for 120 seconds of observations.